Memahami Pola Perkembangan Motorik Pada Anak Usia Dini - Riris Eka Setiani (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2013)
Abstract: Golden period, a phase which is essential for the growth and development of children. Not all parents and teachers have been comprehensively understand the importance of the golden period of development at an early age. As an important future, past all the potential sensitivity of children to thrive. Therefore, it would need to support an environment conducive to the development potential of children. Developments that first occurred in children are physical-motor development, motor development of the child within the meaning along with physical growth. Infants and children develop the skills of rolling, sitting, standing, and other motor skills in a fixed order and according to the specified time range. It is very important to be known by the parents and other educators. This discussion approach life. Motor skills are not developed an ability for granted, but rather through a process of learning and practice. Have motor development principles in its development so that there is a logical consequence of the development of such skills as motor development in childhood has a function and hazard category in its development that may result in physical or psychological harm. Understand it to be a necessity in order to avoid delays in the development of early childhood motor skills. Keywords: development, motor, child.